(3LGeY GdCMcGe aj eYQaI GdMdGd hGdMQGes - (3YHO Gddg Hf eMeO QVG THQ GdMSjfj GdcGXej,J (B1242 (3g` s
(3ChdgG (B:s
(3CeG HYO gPG gh GdeLdO GdKGef ef LGeY GdMcGe ai eYQaI GdMdGd hGdMQGe s
(3BNQgG (B:s
(3Je cJGH GdeWGYe hGdeTGQH ef LGeY GdCMcGe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B131 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B118s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis